2022
DOI: 10.1039/d2gc00640e
|View full text |Cite
|
Sign up to set email alerts
|

Near quantitative conversion of xylose into bisfuran

Abstract: Renewable and abundant carbohydrates are promising feedstocks for producing valuable chemicals. Here we report a highly efficient Zr-catalysed conversion of xylose and acetylacetone (acac) to a new type of bisfuranic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Moreover, it has the ability to operate as a combined acid catalyst for both Lewis and Brønsted acids because ZrCl 4 can react with water to form ZrOCl 2 •8H 2 O and HCl. 8,48 Several studies have suggested possible mechanisms for the conversion of different carbohydrates (e.g., fructose, glucose, cellulose, GlcN, and chitosan) into 5-HMF and LA through complicated and consequential pathways. 2,6,8,16,17,20,34,35,39 The dehydration process is well understood for the conversion of fructose into 5-HMF.…”
Section: Time Course Of the Formation Of Platform Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has the ability to operate as a combined acid catalyst for both Lewis and Brønsted acids because ZrCl 4 can react with water to form ZrOCl 2 •8H 2 O and HCl. 8,48 Several studies have suggested possible mechanisms for the conversion of different carbohydrates (e.g., fructose, glucose, cellulose, GlcN, and chitosan) into 5-HMF and LA through complicated and consequential pathways. 2,6,8,16,17,20,34,35,39 The dehydration process is well understood for the conversion of fructose into 5-HMF.…”
Section: Time Course Of the Formation Of Platform Chemicalsmentioning
confidence: 99%
“…It is known that ZrCl 4 can react with water to form ZrOCl 2 •8H 2 O and HCl. 8,48 The Lewis acidic Zr 4+ cation is mostly responsible for the catalytic activity, whereas HCl as a Brønsted acid may be advantageous for the subsequent dehydration. 48 It is possible that the produced HCl might function as a strong acid for the deacetylation of GlcNAc.…”
Section: Time Course Of the Formation Of Platform Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Similarly, γ-hydroxy-α,β-unsaturated ketones formed through in situ Knoevenagel condensation of 1,3-diketones and α-hydroxyaldehydes undergo facile cyclisation and elimination to form highly substituted furans, a process that is used in the valorisation of aldose sugars (known as the Garcia-Gonzalez reaction). 9…”
Section: Introductionmentioning
confidence: 99%
“…Xylose is the main component of hemicellulose and the second most abundant sugar in nature after glucose ( Zhao et al, 2020 ; Kawaguchi et al, 2006 ). Xylose is widely used in food ( Sasanam et al, 2021 ; Corim Marim and Gabardo, 2021 ), medicine ( Zhou and Murphy, 2010 ; Cheudjeu, 2020 ; Chen et al, 2020 ), and chemical industry ( Zhang et al, 2022a ; Wang et al, 2022 ) as food additive ( Sasanam et al, 2021 ; Corim Marim and Gabardo, 2021 ), drug excipients ( Cheudjeu, 2020 ), and feedstock ( Zhou and Murphy, 2010 ; Chen et al, 2020 ; Zhang et al, 2022a ; Wang et al, 2022 ). In addition, xylose can also be used as carbon and energy for microbial metabolism and growth.…”
Section: Introductionmentioning
confidence: 99%